The Benefits of Pedagogical Translation on Learning the personal a in Spanish - Iranzo, Vicente (2023)
Over the last few years, educators have been witnessing how pedagogical translation is being reincorporated into the language classroom (Carreres et al., 2018; Pintado Gutiérrez, 2020). The present study examines the effects of pedagogical translation on learning the personal a in Spanish, also known as Differential Object Marker (DOM), a grammatical property that posits a challenge for English-speaking learners of Spanish (Bowles & Montrul, 2009), even among speakers who have resided in a Spanish-speaking community for an extended period of time. To this end, 10 anglophone advanced learners of Spanish, enrolled at a public universityin Utah, completed a pretest, an immediate posttest, and a delayed posttest that examined their knowledge of the personal a in Spanish. Quantitative analyses revealed that the advanced second language learners clearly benefited from the use of pedagogical translation (English>Spanish) in the classroom. Our findings are in line with those of Gasca Jiménez (2017) and Barbasán Ortuño et al. (2018) and contribute to the existing literature on pedagogical translation that highlights the benefits of translation in language learning and unreservedly advocates for the use of translation in the language classroom.